Development and Usability Evaluation of a Desktop Software Application for Pain Assessment in Infants. Issue 1 (1st January 2018) - Hundert, Amos S.; Campbell-Yeo, Marsha; Brook, Harrison R.; Wozney, Lori M.; O'Connor, Kelly
ABSTRACT: Background: Pain assessment is a key component of pain management and research in infants. We developed software to assist in coding of pain in infants called PAiN (Pain Assessment in Neonates). Aims: The aims of this study were to evaluate the usability of PAiN in terms of effectiveness, efficiency, and satisfaction among novice and expert users and to compare the efficiency and satisfaction of PAiN to existing software for coding of infant pain among expert users. Methods: A quantitative usability testing approach was conducted with two participant groups, representing novice and expert end-users. Testing included an observed session with each participant completing a pain assessment coding task, followed by administration of the Post Study System Usability Questionnaire and Desirability Toolkit. For comparison, the usability of existing coding software was also evaluated by the expert group. Results: Twelve novice and six expert users participated. Novice users committed 14 noncritical navigational errors, and experts committed six. For experts, the median time for completing the coding task was 28.6 min in PAiN, compared to 46.5 min using the existing software. The mean Post Study System Usability Questionnaire score among novice (1.89) and expert users (1.40) was not significantly different ( P = 0.0917). Among experts, the score for the existing software (4.83) was significantly ( P = 0.0277) higher compared to PAiN (1.40). Lower scores indicate more positive responses. Conclusions: Users were highly satisfied with PAiN. Experts were more efficient with PAiN compared to the existing software. The study was critical to ensuring that PAiN is error free and easy to use prior to implementation.